Pengaruh Pendidikan Karakter, Pola Asuh, dan Pergaulan dengan Teman Sebaya terhadap Prestasi Belajar Matematika - Wahyuni, Nur; Siswanto, Deny Hadi; Tarso, Tarso (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
This study aims to: (1) analyze the influence of character education on learning outcomes, (2) analyze the influence of parenting patterns on learning outcomes, and (3) analyze the influence of peer relationships on learning outcomes. This study was conducted at Muhammadiyah Mlati Senior High School with a sample of 30 students of grade XI Natural Sciences and using a quantitative approach with a descriptive method. The results of the data analysis showed that all of these external factors had a positive influence on student learning achievement. First, character education made a significant contribution, where better character education instillation methods had an impact on improving student learning achievement. Second, good parenting patterns, especially in supporting and supervising student learning development, also played a role in improving learning achievement. Third, healthy and supportive peer relationships also had a positive impact on student learning achievement. The better the social relationships between students, the better the learning achievement they obtained.